Ratio Legis Perbedaan Rumusan Delik Pasal 2 dan Pasal 3 Undang-Undang Nomor 31 Tahun 1999 Jo. Undang-Undang No. 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi - Gatot Triyanto (JURNAL RECHTENS, 2017)
The qualification of criminal acts of corruption is as stated in Article 2 and Article 3 of Law no. 31 year 1999 jo. UU no. Law No. 20 of 2001. In further detail, according to Article 2, the meaning  of  a  criminal  act  of  corruption  has  the  following  elements:  Every  person; Unlawfully; Perform an enriching act of self or another person or a corporation; Which can harm the state finance or state economy. Whereas according to Article 3 the elements of corruption acts, are as follows: Every person; For the purpose of benefiting oneself or others or a corporation; Abuses any authority, opportunity or means available to him due to position or position, which may harm the state's finances or the economy of the country. Article 2 and Article 3 mentioned above, there are differences and similarities. The equality of the two chapters lies in the imposition of the "Everyone" and the Elements "may harm the state economy and state finances". As for the difference lies in the formulation of Article 2 which states the phrase "unlawfully" and "enrich themselves or others or a corporation", while the formulation of article 3 includes the phrase "Abusing the authority, opportunity or means available to him because of position or position "And" to benefit oneself or others or a corporation. "